Analisis Jalur Pada SDGs Terhadap IPM di JawaTimur - Aulia Daisy Arsy Syafitri; Ririt Iriani Sri Setiawati (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study examines the influence of Sustainable Development Goals (SDGs) indicators on the Human Development Index (HDI) across the ten highest-ranked districts/cities in East Java from 2020 to 2023. The primary issue addressed is the inconsistency between the Labor Force Participation Rate (LFPR) and HDI achievement, despite consistent correlations between Life Expectancy (LE), Mean Years of Schooling (MYS), and HDI. The objective is to analyze both the direct and indirect relationships between LE, LFPR, and MYS on HDI, and to assess the mediating role of MYS. A quantitative explanatory approach is employed using path analysis and panel data regression, with the Random Effect Model selected based on Chow, Hausman, and Breusch-Pagan tests. The results show that LE and MYS have a significant positive impact on HDI, while LFPR does not. Additionally, MYS partially mediates the relationship between LE and HDI but does not mediate the link between LFPR and HDI. These findings reinforce human capital theory, health capital theory, and sustainable development theory, highlighting education and health as central to human development. The study concludes that enhancing education and health quality has a more substantial impact on HDI improvement than increasing labor force participation alone, suggesting that development policies in East Java should strategically prioritize these sectors to accelerate SDGs achievement.